Organisational Lessons from Jazz Musicians: It Don't Mean A Thing (If It Ain't Got That Swing). - Legair, Marielle (2007)
The aim of this study is to present and analyse the experienced phenomenon of professional jazz musicians. With particular attention devoted to jazz musicians' approach to leadership, creativity and innovation. The study adopted an original and innovative method of data collection using MySpace, the social networking website to contact research subjects, i.e. professional jazz musicians. Data was collected through use of in-depth semi structured interviews with sixteen jazz musicians and observation of The Lincoln Centre Jazz Orchestra (LCJO). The author is reflexive about the research process and the role the authors' personal characteristics may have had on the research process. Data was analysed by identifying the emergent themes that had arisen from the data. A case study is presented through use of data-rich verbatim quotes. The study answers the following research questions: What can the leadership approach of a jazz band add to the existing leadership literature? What can the study of jazz ensembles contribute to the existing theory of creativity and innovation in organisational teams? How accurately does the current organisational jazz literature reflect the characteristics of a modern jazz ensemble? The conclusion of this paper indicates that organisational leaders can draw on the approaches used by jazz musicians in order to create and sustain creative and innovative practices in their work.